1990
DOI: 10.1103/physrevlett.65.191
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of a lipid monolayer on the surface of water

Abstract: The monolayer isotherms of heneicosanoic acid show a variety of features in the range 1-8 °C; such features are often assumed to be solid-fluid or fluid-fluid transitions. Using x-ray diffraction (and searching for in-plane and off-plane peaks) we find (a) two distinct distorted-hexagonal (DH) solids at high pressures, both with essentially vertical chains; (b) two distinct tilted-DH solids at intermediate pressures; and (c) an expanded solid at the lowest pressures. All "plateaus" in these isotherms are inpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(107 citation statements)
references
References 11 publications
4
102
1
Order By: Relevance
“…Such an increase in the tilt angle upon compressing a monolayer of long chain molecules (fatty alcohols and acids) was calculated on the basis of X-ray measurements. [18][19][20] In the stable -phase, the triglyceride molecules are tilted at tilt angle τ ) 60.8°. 8 Because presumably in the trident monolayer the alkyl chains are less densely packed than the crystalline phases, a smaller tilt angle seems acceptable.…”
Section: Monolayer Thicknessmentioning
confidence: 99%
“…Such an increase in the tilt angle upon compressing a monolayer of long chain molecules (fatty alcohols and acids) was calculated on the basis of X-ray measurements. [18][19][20] In the stable -phase, the triglyceride molecules are tilted at tilt angle τ ) 60.8°. 8 Because presumably in the trident monolayer the alkyl chains are less densely packed than the crystalline phases, a smaller tilt angle seems acceptable.…”
Section: Monolayer Thicknessmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][32][33][34] Except for a few cases, which have hexatic order, most of these phases exhibit resolution-limited Bragg peaks characteristic of 2D crystalline phases. Figure 1͑b͒ contains a schematic illustration of the kinematics for the GID experiment.…”
Section: ͑1͒mentioning
confidence: 99%
“…1-3 A principal challenge in this general area of physics has been to identify real, well defined physical systems that are suitable for experimental studies. Examples of two-or quasi-twodimensional systems that have been investigated for this purpose in recent years include rare gases adsorbed on solid substrates, [3][4][5][6] freely suspended thin liquid crystal films, [7][8][9][10] and Langmuir monolayers 11,12 of simple long-chain molecules such as fatty acids, [13][14][15][16][17][18][19][20][21][22][23] alcohols, [24][25][26][27] esters, 28 etc. Related statistical phenomena at surfaces and interfaces that have been often studied for more practical motivations, include wetting, [29][30][31] premelting and reconstruction of crystalline surfaces, [32][33][34][35] and surface induced order at liquid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Although many phase diagrams have been already proposed, [7][8][9][10][11][12][13] it is not clear that any of these are truly equilibrium diagrams. The question arises because, in almost all of the phase diagrams published, the monolayer is compressed continuously, at a constant rate, without allowing sufficient time for the surface pressure to relax to an equilibrium value.…”
Section: Introductionmentioning
confidence: 99%
“…24 Finally, Foster et al determined the phase diagram for a relaxed Langmuir monolayer of methyl eicosanoate ͑CH 3 ͑CH 2 ͒ 18 COOCH 3 ͒; and found that although the topology of the relaxed phase diagram for this long chain fatty ester is in good agreement with previous work published for this system, the relaxed monolayer exhibits an additional phase previously unreported. 25 An important difference between the work presented here and most of the others [7][8][9][10][11][12][13] is that thermodynamic information is collected simultaneously with x-ray measurement of the microscopic structure, and both are combined to ensure that the results are self-consistent.…”
Section: Introductionmentioning
confidence: 99%